Renal NKCC2 Is Dual Regulated by the Synergy of 20-HETE and High-Fat Diet in CYP4F2 Transgenic Mice - Jingjing Wu; Guangrui Lai; Fangjie Chen; Bijun Zhang; Yanyan Zhao (Karger Publishers, 2021)
Introduction: 20-Hydroxyeicosatetraenoic acid (20-HETE) is the metabolite of cytochrome P450, which modulates blood pressure by inhibiting renal sodium transport. However, the molecular mechanisms underlying the role of 20-HETE in the development of obesity-related hypertension remain unclear, necessitating this study. Methods: Cytochrome P450 4F2 (CYP4F2) transgenic mice fed high-fat diet (HFD) were used as research animal models. The expression of renal ion transport molecules targeted by 20-HETE was evaluated by real-time PCR and Western blot (WB). The regulatory effect of 20-HETE and HFD on renal Na+-K+-2Cl− cotransporter, isoform 2 (NKCC2) was explored by immunoprecipitation, WB, and luciferase assay. Results: A 2-week HFD feeding dramatically decreased protein abundance but increased renal NKCC2 mRNA expression in CYP4F2 transgenic mice. The decrease in NKCC2 protein was demonstrated to be due to ubiquitination induced by the synergy between 20-HETE and HFD. The increased PPAR-γ protein in CYP4F2 transgenic mice fed HFD and the activation of rosiglitazone on the luciferase reporter construct of the NKCC2 promoter demonstrated that the increase in NKCC2 mRNA in CYP4F2 transgenic mice fed HFD was a consequence of elevated PPAR-γ protein induced by the synergy between 20-HETE and HFD. Conclusions: Our data demonstrated that the synergy between 20-HETE and HFD could decrease NKCC2 protein via posttranslational ubiquitination, which was thought to be the main mechanism underlying the short-term effect in response to HFD and might be responsible for the adaptive modulation of renal NKCC2 to resist sodium retention. Moreover, the increased NKCC2 mRNA expression via PPAR-γ-induced transcriptional regulation was thought to be the main mechanism underlying the long-term effect in response to HFD and plays a pivotal role in the development of obesity-related hypertension.